Efficacy of eugenol as anesthetic in the chame Dormitator latifrons maintained at two salinities - Zambrano-Bermúdez, Daniela (2023)
The aim of this study was to evaluate the induction and recovery time of Dormitator. latifrons maintained in fresh and brackish water, exposed to four doses of eugenol. A total of 240 organisms were individually transferred to an aquarium with 15 L of fresh water (0 UPS) or brackish water (20 UPS) with the eugenol dose of each treatment (42.5, 85, 170 and 255 mg/L). In each treatment, 30 fish were analysed. The induction time did not show significant differences between salinity levels, while the recovery time was significantly higher in brackish water (706 s) than in fresh water (507 s) (p<0.05). In both salinities, increasing the eugenol dose decreases the induction time and increases the recovery time. The results indicate that the effective dose of eugenol for D. latifrons is 170 mg/L in both salinities; however, for short-term procedures, immersion at a dose of 42.5 mg/L would be sufficient to achieve sedation.